Pengaruh Model TPS Terhadap Peningkatan Keaktifan Dan Kerja Sama Siswa SMB Pada Materi Jalan Utama Berunsur Delapan - Metta Wiji Astuti; Mujiyanto Mujiyanto; Dwi Maryani Rispatiningsih (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
The activeness and cooperation of students is one of the factors for students to understand a material well. Therefore it is necessary to increase student activity and collaboration. For this reason, there is a need for a learning model that can increase student activity and cooperation. One of the learning models that can increase student activity and collaboration is the cooperative learning model Think Pair Share type (TPS), because this cooperative learning model emphasizes student cooperation and discussion in groups and in learning divides students into small groups consisting of 2 students. This study aims to: 1) To determine the effect of the Think Pair Share Cooperative Learning Model on student activity To determine the effect of the Think Pair Share Cooperative Learning Model on student cooperation. This type of research is a type of quantitative research that will use ANOVA analysis. The sample used in this study amounted to 16 students in the three SMBs in the Seputih Raman sub-district. Data collection techniques in this study using questionnaires or questionnaires, interviews and observations. Based on the results of the analysis conducted by researchers that F count the activity of F table (0.459 3.81) then Ho is accepted. The results of these calculations can be defined that the TPS learning model has no effect on increasing the activity of SMB students. The results of these calculations can be defined that the TPS learning model does not increase the cooperation of SMB students